On Interval-Valued Pseudolinear Functions and Interval-Valued Pseudolinear Optimization Problems - Jianke Zhang; Qinghua Zheng; Chang Zhou; Xiaojue Ma; Lifeng Li (Journal of Function Spaces)
Some basic characterizations of an interval-valued pseudolinear function are derived. By means of the properties of interval-valued pseudolinearity, a class of interval-valued pseudolinear programs is considered, and the solution set of the interval-valued pseudolinear optimization problem is characterized.